Identification and characterization of Sr59-mediated stem rust resistance in a novel wheat-rye translocation T2BL·2BS-2RL - Mahboobeh Yazdani; Matthew N. Rouse; Prabin Bajgain; Tatiana V. Danilova; Ivan Motsnyi; Brian J. Steffenson; Mehran Patpour; Mahbubjon Rahmatov (Crop Journal)
Emerging new races of wheat stem rust (Puccinia graminis f. sp. tritici) are threatening global wheat (Triticum aestivum L.) production. Host resistance is the most effective and environmentally friendly method of controlling stem rust. The stem rust resistance gene Sr59 was previously identified within a T2DS·2RL wheat-rye whole arm translocation, providing broad-spectrum resistance to various stem rust races. Seedling evaluation, molecular marker analysis, and cytogenetic studies identified wheat-rye introgression line #284 containing a new translocation chromosome T2BL·2BS-2RL. This line has demonstrated broad-spectrum resistance to stem rust at the seedling stage. Seedling evaluation and cytogenetic analysis of three backcross populations between the line #284 and the adapted cultivars SLU-Elite, Navruz, and Linkert confirmed that Sr59 is located within the short distal 2RL translocation. This study aimed physical mapping of Sr59 in the 2RL introgression segment and develop a robust molecular marker for marker-assisted selection. Using genotyping-by-sequencing (GBS), GBS-derived SNPs were aligned with full-length annotated rye nucleotide-binding leucine-rich repeat (NLR) genes in the parental lines CS ph1b, SLU238, SLU-Elite, Navruz, and Linkert, as well as in 33 BC4F5 progeny. Four NLR genes were identified on the 2R chromosome, with Chr2R_NLR_60 being tightly linked to the Sr59 resistance gene. In-silico functional enrichment analysis of the translocated 2RL region (25,681,915 bp) identified 223 genes, with seven candidate genes associated with plant disease resistance and three linked to agronomic performance, contributing to oxidative stress response, protein kinase activity, and cellular homeostasis. These findings facilitate a better understanding of the genetic basis of stem rust resistance provided by Sr59.